2014
DOI: 10.1016/j.jfa.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

On differential operators associated with Markov operators

Abstract: In this paper we introduce and study a new class of elliptic second-order differential operators on a convex compact subset K of R^d, d\geq 1, which are associated with a Markov operator T on C(K) and which degenerate on a suitable subset of K containing its extreme points. Among other things,\ud we show that the closures of these operators generate Markov semigroups. Moreover, we prove that these semigroups can be approximated by means of iterates of suitable positive linear operators, which are referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They prove that the closure A of the operator V generates a Feller semigroup true{Tttrue}t0 and further that the Feller semigroup true{Tttrue}t0 can be approximated by iterates of modified Bernstein–Schnabl operators ([4]). It should be emphasized that Theorem 1.2 coincides with [2, Theorem 4.1], [3, Theorem 4.3] and [5, Theorem 3.1] with K:=D if the boundary K is smooth, as in Example 1.1. 2°Theorem 1.2 is proved by Bony–Courrège–Priouret [8] in the elliptic case (see [8, Théorème XVI]) and then by Cancelier [9] in the non‐characteristic case: D=normalΣ3 (cf. [9, Théorème 7.2]).…”
Section: Introduction and Main Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…They prove that the closure A of the operator V generates a Feller semigroup true{Tttrue}t0 and further that the Feller semigroup true{Tttrue}t0 can be approximated by iterates of modified Bernstein–Schnabl operators ([4]). It should be emphasized that Theorem 1.2 coincides with [2, Theorem 4.1], [3, Theorem 4.3] and [5, Theorem 3.1] with K:=D if the boundary K is smooth, as in Example 1.1. 2°Theorem 1.2 is proved by Bony–Courrège–Priouret [8] in the elliptic case (see [8, Théorème XVI]) and then by Cancelier [9] in the non‐characteristic case: D=normalΣ3 (cf. [9, Théorème 7.2]).…”
Section: Introduction and Main Resultsmentioning
confidence: 88%
“…This paper is inspired by the work of Altomare et al. [2, 3] and [5] (see Remark 1.3), and it is a continuation of the previous papers Taira [23] through [31] and Taira–Favini–Romanelli [32].…”
Section: Introduction and Main Resultsmentioning
confidence: 93%
“…The iterates converge to the linear interpolation operator that interpolates at the endpoints of [0,1]. In this example we demonstrated the underlying framework for finite-rank operators that reproduce constant and linear functions.…”
Section: An Introductory Examplementioning
confidence: 84%
“…Recently, Altomare [2] has shown a different approach using the concept of Choquet-boundaries and results from Korovkin-type approximation theory. Altomare et al [1] have shown an application where they discussed differential operators associated with Markov operators, where also the knowledge of limit of the iterates is significant. Another application has been shown in the field of approximation theory, where the iterates can be used to prove lower estimates for Markov operators with sufficient smooth range, see Nagler et al [17].It is worthwhile to mention that in most methods the limiting operator has to be known apriori.…”
mentioning
confidence: 99%
“…In the above mentioned works, though, it was assumed that the underlying operator T is a positive projection satisfying suitable assumptions. Francesco overcame such a limitation first in the context of the interval [0, 1], in the joint work [23] with the second author of this paper and Ioan Raşa, and then in the context of compact convex sets of R d (see [18,20]).…”
Section: Some Important Scientific Contributions Of Francesco Altomarementioning
confidence: 99%